Contemporary Issues in the Provisions of Neighborhood - Ali Fakher (Journal of Umm Al-Qura University for Shari'ah Sciences and Islamic Studies, 2023)
In light of the significant development in various fields in our recent time and the occurrence of contemporary emerging issues in the relationship between neighbours and the disputes that may result from them, this research titled "Contemporary Issues in the Rulings on Neighborhood" came to treat the contemporary issues in the rulings on neighbourhood and study them through an Islamic perspective by establishing, drawing inference and explaining their rulings and the sayings of contemporary scholars regarding them, explaining their jurisprudential description. The research also aims to benefit specialised researchers and others by dealing with emerging contemporary jurisprudential issues. This research adopted an inductive approach by searching for contemporary emerging issues in the rulings on neighborhood and the problems that arise from them, and a deductive and analytical approach by deducting the reasons for the Islamic rulings mentioned by the jurists in the rulings on neighbourhood and measuring the contemporary emerging issues on them and giving them the correct jurisprudential description. Among the most important findings of the research is that a neighbour has the right to use his property without harming the neighbour. From the Islamic perspective, a neighbourly relationship is a solid relationship based on kindness. The right of the neighbour in Islam forbids transgression against him. The research recommended the importance of studying contemporary emerging issues that are frequently needed, especially in the aspect of transactions with others, such as those that occur between neighbours in the house and other transactions.